HUBUNGAN ANEMIA PADA IBU HAMIL DENGAN KEJADIAN PREEKLAMSIA DI RSUD ARIFIN ACHMAD PEKANBARU - Syamsul Bahri Rivai; Alifia Gusrizka Sandrina; Soraya Medina Ruza; Mofrilindo Mofrilindo (Collaborative Medical Journal, 2025)
Preeclampsia is one of the most common health problems in pregnancy. The incidence of preeclampsia in Indonesia alone reaches 128,273 per year or around 5.3%. WHO estimates that the incidence of preeclampsia in developing countries is 2.8% compared to 0.4% in developed countries (Rijal, 2017). The prevalence rate of anemia in pregnant women worldwide is 43.9%. Indonesia is a developing country with a fairly high prevalence of anemia, namely 48.9% in pregnant women. 13.1% of pregnant women in Riau Province were diagnosed as suffering from anemia. In 2015, WHO published that 83.2% of pregnant women globally experienced anemia, while in Indonesia itself it is estimated that anemia can occur in 30% of pregnant women. According to the 2017 WHO report, the maternal mortality rate (MMR) in the world is 289,000 people. Meanwhile, MMR in Riau Province recorded 180 cases of maternal death in 2021. The prevalence of anemia in pregnancy is 40% globally. Meanwhile, MMR caused by severe preeclampsia and eclampsia in a number of developing countries is still quite high. In Indonesia, severe preeclampsia and eclampsia are the causes of 30-40% of maternal deaths. This study aimed tto determine the relationship between anemia in pregnant women and the incidence of preeclampsia at Arifin Achmad Hospital Pekanbaru. This type of research is quantitative observational analytic, with a retrospective cohort study design using a total sampling method. There is no relationship between anemia in pregnancy and insidence of preeclampsia (p = 0,169).